Lecture capture: An effective tool for universal instructional design? - Vajoczki, Susan; Watt, Susan; Fenton, Nancy; Tarkowski, Jacob; Voros, Geraldine; Vine, Michelle M. (Canadian Journal of Higher Education, 2014)
Student enrolment and instructional accommodation requests are rising in higher education. Universities lack the capacity to meet increasing accommodation needs, thus research in this area is required. In Ontario, new provincial legislation requires that all public institutions, including universities, make their services accessible to persons with disabilities. The objective of the Accessibility for Ontarians with Disabilities Act (AODA) is to provide universal access for students with disabilities. The purpose of this case study is to understand the experiences of students regarding the ability of a lecture capture technology to align with the principles of Universal Instructional Design (UID). Data were collected using a mixed-method research design: (a) an online questionnaire, and (b) individual face-to-face interviews. Scholarship of Teaching and Learning (SoTL) literature provides a useful background to explore AODA legislation and universal accessibility vis-à-vis lecture capture technologies. Results indicate that lecture capture can align both with the principles of UID and AODA.